SORUŞTURMA GRUBUNDA GÖREV YAPAN İL EĞİTİM DENETMENLERİNİN SÜREÇ İÇİNDE KARŞILAŞTIKLARI SORUNLAR - (:unkn) unknown (My University, 2017)
Bu çalışmanın amacı, İstanbul'da görev yapan soruşturma grubundaki il eğitim denetmenlerinin disiplin soruşturmalarında karşılaştıkları sorunların neler olduğunun incelenmesidir. Araştırma, içerik analiz yönteminin benimsendiği nitel bir çalışmadır. Araştırmanın çalışma grubunu, İstanbul İl Eğitim Denetmenleri Başkanlığına bağlı 77 soruşturma grubunda, ikili olarak görev yapan 154 il eğitim denetmeninden gönüllü olarak katılım sağlayan 27 il eğitim denetmeni oluşturmaktadır. Araştırmada, Özmen ve Şahin (2010) tarafından hazırlanan, 9 maddelik açık uçlu sorulardan oluşan veri toplama aracı kullanılmıştır. değerlendirilmiştir. Verilerin sunulmasında konu alanlarına göre frekans sayısı dikkate alınarak sıralama yapılmış ve il eğitim denetmenlerinin çarpıcı olan görüşleri detaylı bir biçimde verilmiştir. Sonuç olarak görevlendirme emirlerinde konuların açık ve net olarak belirtilmemesi ve bilgi-belge eksiklikleri nedeni ile il eğitim denetmenleri sıkıntılar yaşamaktadır. Soruşturmanın yürütülmesi aşamasında, şikâyetçilerin kendilerini gizlemeleri ve yanlış adres, isim ve telefon vermeleri, iddiaların genel anlamda duyuma dayanması, bilgi ve belgelerle desteklenmemesi, işlerin kalitesini düşürmektedir. Birçok konuda mevzuatın birbiriyle çelişmesi; denetmenler arasında görüş farklılıklarının olması; uygulamada birlik sağlanmaması, karşılaşılan önemli sorunlar olarak görülmüştür

The purpose of this study is to determine the problems faced by provincial educational supervisors, who are working in the investigation group in Istanbul, during the process of disciplinary investigations. The study was conducted as a qualitative study using descriptive survey model. Among 154 provincial educational supervisors that worked in couples in 77 investigation groups under Istanbul Provincial Educational supervisors Directorate, 27 provincial educational supervisors volunteered in the study constituting the study group. Data collection tool developed by Özmen and Şahin (2010) consisting of 9 open-ended questions was used in the study. The data collected was evaluated using content analysis. The presented data was ordered based on the frequencies in subject fields and the outstanding views of the provincial educational supervisors were offered in detail. The findings demonstrated that problems were encountered during the conduction of the inspections due to the vagueness of the assignment orders and lack of information and documentation. It was determined that during the implementation of the investigation, the anonymity of the complainants providing false names, addresses and phone numbers; complaints mostly being based on hearsay, not substantiated by information and documentation, decreased the quality of work done. The most significant issues confronted by the supervisors were conflicting regulations, differences of opinion among supervisors, inconsistency in implementation due to issues pertaining to regulations
THE PROBLEMS FACED BY PROVINCIAL EDUCATIONAL SUPERVISORS WORKING IN THE INVESTIGATION GROUP DURING THE PROCESS
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel